1990
DOI: 10.1111/j.1467-8624.1990.tb02815.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Understanding of the Modal Expression of Speaker Certainty and Uncertainty and Its Relation to the Development of a Representational Theory of Mind

Abstract: 2 experiments examined children's understanding of the expression of speaker certainty and uncertainty and its relation to their developing theory of mind. In the first experiment, 80 children between 3 and 6 years of age were presented with a task in which they had to guess the location of an object hidden in 1 of 2 boxes. As clues to location, the children were presented with contrasting pairs of statements by 2 puppets. Different trials contained all of the possible pairwise combinations of either the modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
117
1
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 18 publications
10
117
1
9
Order By: Relevance
“…Furthermore, the relationship between theory of mind (characterised by numerous concepts of reality and the existence of varying viewpoints apart from one's own (e.g., Flavell 2004, Wellman 1990) and language acquisition has been discussed intensively (e.g., Miller 2006, Milligan et al 2007. Specifically, children's abilities to use different epistemic markers are connected with the development of so-called modal language (including mental state vocabulary), belonging to an explicit theory of mind (Brooks, Meltzoff 2015, Moore et al 1990, Moore, Furrow 1991, Öztürk, Papafragou 2015, Papafragou 1998, Ruffman et al 2006, Taumoepeau, Ruffman 2016. However, only the children's understanding of the expression of the speaker's certainty and uncertainty has been examined (usually experimentally).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between theory of mind (characterised by numerous concepts of reality and the existence of varying viewpoints apart from one's own (e.g., Flavell 2004, Wellman 1990) and language acquisition has been discussed intensively (e.g., Miller 2006, Milligan et al 2007. Specifically, children's abilities to use different epistemic markers are connected with the development of so-called modal language (including mental state vocabulary), belonging to an explicit theory of mind (Brooks, Meltzoff 2015, Moore et al 1990, Moore, Furrow 1991, Öztürk, Papafragou 2015, Papafragou 1998, Ruffman et al 2006, Taumoepeau, Ruffman 2016. However, only the children's understanding of the expression of the speaker's certainty and uncertainty has been examined (usually experimentally).…”
Section: Introductionmentioning
confidence: 99%
“…3 Third, the idea that a listener would reject a strong interpretation when it is provided seems unlikely. Many have shown (Hirst & Weil 1982;Moore et al 1990;Noveck et al 1995, Chierchia et al 2004) that children, at least, prefer stronger utterances over weak ones in the absence or presence of validating context. For example, Noveck et al (1995) showed how five-year-olds prefer to follow the advice of the speaker who uses has to over another who uses might when there is no way to determine which is correct (compare The peanut has to be under the cup versus the peanut might be under the box) and Chierchia and colleagues have shown that four-year-olds prefer stronger descriptions over weak ones when both options are valid (for example they choose all over some to describe a scenario that would best be described with all).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that language plays a crucial role in theory-of-mind development, especially false-belief understanding, has come from correlational (Astington & Baird, 2005;de Villiers & de Villiers, 2000;Moore, Pure, & Furrow, 1990) and training studies (Hale & Tager-Flusberg, 2003;Lohmann & Tomasello, 2003). Although the direction of this relationship is still hotly debated (Milligan, Astington, & Dack, 2007) and the effect of language on theory of mind seems to be stronger than the other way around, recent findings support the hypothesis of a bidirectional relationship between theory of mind and language (Slade & Ruffman, 2005).…”
Section: Introductionmentioning
confidence: 99%